Austria : Financial Sector Assessment Program Technical Note; Stress Testing and Short-Term Vulnerabilities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This technical note focuses on the Austrian banking system that exhibits considerable resilience against shocks determined by stress tests. The main sources of risk lie in the credit risk arising from exposures to Central, Eastern, and Southeastern Europe (CESE) and the Commonwealth of Independent States (CIS), indirect credit risk from foreign currency lending, and credit risk from domestic lending. The Austrian banking systems exhibits ample liquidity. In-depth discussions with the larger banks show that their modeling capacities vary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet